Student engagement in urban schools : beyond neoliberal discourses - McMahon, Brenda J.; Portelli, John P. (Issues in the research, theory, policy, and practice of urban education., 2012)
The focus of this book extends the discourse on student engagement beyond prescriptive definitions and includes substantive ethical and political issues relating to this concept. As such, this collection includes voices of educational theorists, practitioners, and students. It provides a counter discourse to the current dialogue on student engagement in educational theory and practice which equate it primarily with behavioral and attitudinal characteristics including student compliance and qualities of teaching or teachers.In this collection, engagement is not viewed simply as a matter of techniques, strategies or behaviours. Rather, the understandings of student engagement presented, while distinct from each other, are imbued with a common vision of education for democratic transformation or reconstruction as operational for and in democratic communities. Contributors to this volume examine issues of the purpose of student engagement, and the question of the criteria, standards, and norms which are used to determine the quality and degree of engagement, and ultimately whether or not all forms of student engagement are equally worthwhile. This collection is intended for use in teacher and administrator preparation programs as well as school and district professional development initiatives.